2016
DOI: 10.1681/asn.2015070763
|View full text |Cite
|
Sign up to set email alerts
|

Race, APOL1 Risk, and eGFR Decline in the General Population

Abstract: The APOL1 high-risk genotype, present in approximately 13% of blacks in the United States, is a risk factor for kidney function decline in populations with CKD. It is unknown whether genetic screening is indicated in the general population. We evaluated the prognosis of APOL1 high-risk status in participants in the population-based Atherosclerosis Risk in Communities (ARIC) study, including associations with eGFR decline, variability in eGFR decline, and related adverse health events (AKI, ESRD, hypertension, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
129
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 129 publications
(139 citation statements)
references
References 38 publications
9
129
1
Order By: Relevance
“…We found no association between the APOL1 risk variants and incident MI, coronary heart disease, or stroke. These findings are in accordance with results from the ARIC (Atherosclerosis Risk in Communities) study and SPRINT trial, which also reported no significant association between the APOL1 high‐risk variants and incident or prevalent CVD, respectively 20, 25. On the other hand, the JHS and WHI (Women's Health Initiative) both demonstrated a significantly increased risk for a major adverse cardiovascular event among people with 2 versus 0 APOL1 high‐risk alleles,21 whereas the CHS noted an increased risk of MI but not stroke or cardiovascular mortality 22.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found no association between the APOL1 risk variants and incident MI, coronary heart disease, or stroke. These findings are in accordance with results from the ARIC (Atherosclerosis Risk in Communities) study and SPRINT trial, which also reported no significant association between the APOL1 high‐risk variants and incident or prevalent CVD, respectively 20, 25. On the other hand, the JHS and WHI (Women's Health Initiative) both demonstrated a significantly increased risk for a major adverse cardiovascular event among people with 2 versus 0 APOL1 high‐risk alleles,21 whereas the CHS noted an increased risk of MI but not stroke or cardiovascular mortality 22.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the JHS and WHI (Women's Health Initiative) both demonstrated a significantly increased risk for a major adverse cardiovascular event among people with 2 versus 0 APOL1 high‐risk alleles,21 whereas the CHS noted an increased risk of MI but not stroke or cardiovascular mortality 22. The reasons for these discrepant findings are unclear, although differences in study populations likely contribute, including varying ages and comorbidities 20, 21, 22, 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,17 Some investigators have also described an increased risk of cardiovascular disease among individuals with two APOL1 high-risk alleles, though this finding has not been consistent across studies. 2629 In addition, Skorecki and Wasser illustrated that the geographic distribution of APOL1 risk variants correlates with the distribution of hypertension prevalence rates in West Africa. 30 Finally, in APOL1 expression studies by Madhavan et al , de novo expression of APOL1 was found in arterial smooth muscle cells of diseased but not healthy kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…The decline of kidney function in the general population and the progression of CKD to ESRD are highly variable (1)(2)(3)(4). Some individuals may experience an unremitting decline in eGFR, whereas others maintain stable eGFR for an extended period (2,3).…”
Section: Introductionmentioning
confidence: 99%